Does tinnitus and emotional distress influence central auditory processing? A comparison of acute and chronic tinnitus in normal-hearing individuals. - Qian Zhou; Wenling Jiang; Haibin Sheng; Qinjie Zhang; Dian Jin; Haifeng Li; Meiping Huang; Lu Yang; Yan Ren; Zhiwu Huang (PLoS ONE, 2025)
Objective Tinnitus is characterized by the perception of sound without an external source and can cause auditory difficulties even in individuals with normal hearing. Design This study compared the auditory afferent and efferent functions of normal-hearing patients with acute tinnitus, chronic tinnitus, and control group using gap detection test, the Mandarin Hearing in Noise Test (MHINT), and contralateral suppression of transient evoked otoacoustic emissions (TEOAEs). Results It reveals the neural and emotional dynamics as tinnitus progresses from acute to chronic stages. Patients with acute and chronic tinnitus exhibited reduced contralateral suppression of TEOAEs, elevated gap detection thresholds, and higher speech recognition thresholds in noisy environments, indicating that tinnitus interferes with both afferent and efferent auditory pathways. The lack of significant differences between acute tinnitus and chronic tinnitus patients suggests that auditory functions do not necessarily deteriorate over time, suggesting that tinnitus may not worsen due to neuroplasticity as the condition progresses. The speech recognition ability in noise of patients with acute tinnitus is influenced by emotional scores, implying that emotional distress plays a crucial role in amplifying tinnitus-related interference. When emotional burden is reduced, the negative feedback loop between emotional distress and neuroplasticity can be broken, preventing further decline in central auditory function. Conclusions These findings highlight the importance of psychological support and emotional management in clinical practice to improve auditory performance and potentially halt the intensification of tinnitus.